The absolute number of circulating Treg cells is reduced in difficult-to-treat RA patients and is ameliorated by low-dose IL-2 - Huanhuan Yan; Huanhuan Yan; Huanhuan Yan; Xiaoyu Zi; Xiaoyu Zi; Xiaoyu Zi; Huer Yan; Xiaoying Zhang; Xiaoying Zhang; Xiaoying Zhang; Jie Bai; Jie Bai; et al. (Frontiers in Immunology)
ObjectiveCirculating regulatory T cells (Tregs) are closely related to immune tolerance and maintenance of immune homeostasis. Perhaps, there is a unique immune cell phenotype for difficult-to-treat rheumatoid arthritis (D2T RA). Low-dose interleukin-2 (IL-2) has been considered for the treatment of autoimmune diseases. This study focused on the uniqueness of D2T RA lymphocyte subsets and the feasibility of low-dose IL-2 therapy.MethodsParticipants included 1,042 RA patients who were divided into three groups according to the presence or absence of treatment and their response to treatment in the last 6 months—new group, treated group, and D2T group—and 339 healthy controls (HCs). A total of 381 patients—107, 151, and 123 in each of the three experimental groups—received low-dose IL-2 treatment [0.5 million international units (MIU) per day, subcutaneous injection from day 1 to day 5]. The absolute numbers of peripheral blood lymphocyte subsets were detected by flow cytometry (FCM) and serum cytokine levels were detected by flow cytometry bead array (CBA).ResultsThe absolute number of T, CD4+ T, and Treg cells in the D2T RA group was lower than that in the HC, new, and treated RA groups. Compared with the HC and new RA group, the ratio of Th17/Treg cells in the D2T RA group increased. The new, treated, and D2T RA groups had higher cytokine levels than the HC. The number of Treg cells in RA patients was negatively correlated with the disease activity index. Treg cells in the new, treated, and D2T RA groups could be increased by low-dose IL-2 therapy without any side effects.ConclusionsThe number of lymphocytes and subsets in D2T RA patients was reduced, especially Treg cells, resulting in a shift in the balance of effector T cells/Treg cells toward effector T cells, which is ameliorated by low-dose IL-2 without obvious side effects.